Application of near - infrared (NIR) spectroscopy to sensor based sorting of an epithermal AU - AG ore - Dalm, M. (KIT Scientific Publishing, 2020)
Test work was performmed with near-infrared (NIR) spectrocopy on 94 ore samples from a South-American Au - Ag mne. The aim of the test work was to investigate if alteration minerals can be detected with the NIR sensor that can be use as indicators of ore value. Partial least squares discriminant analysis (PLS-DA) was applied to the spectral data to make classification models that use the measured NIR spectra to distinguish samples with certain Au, S or C grades. This showed that detection of mineralogy with NIR spectroscopy can be used to discriminate on i ) ore particles with low Au and Ag grades ii) ore particles with high carbon contents iii) ore particle with high sulphide contents